A mineralogical and petrographical investigation of the upper zone of the Busheveld complex, Northwest of Potgietersrus - Von Gruenewaldt, G. (Gerhard), 1942- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1987.